Elucidating regulators of astrocytic Ca2+ signaling via multi‐threshold event detection (MTED). Issue 12 (13th August 2021) - Müller, Franziska E.; Cherkas, Volodymyr; Stopper, Gebhard; Caudal, Laura C.; Stopper, Laura; Kirchhoff, Frank; Henneberger, Christian; Ponimaskin, Evgeni G.; Zeug, Andre
Abstract: Recent achievements in indicator optimization and imaging techniques promote the advancement of functional imaging to decipher complex signaling processes in living cells, such as Ca 2+ activity patterns. Astrocytes are important regulators of the brain network and well known for their highly complex morphology and spontaneous Ca 2+ activity. However, the astrocyte community is lacking standardized methods to analyze and interpret Ca 2+ activity recordings, hindering global comparisons. Here, we present a biophysically‐based analytical concept for deciphering the complex spatio‐temporal changes of Ca 2+ biosensor fluorescence for understanding the underlying signaling mechanisms. We developed a pixel‐based multi‐threshold event detection (MTED) analysis of multidimensional data, which accounts for signal strength as an additional signaling dimension and provides the experimenter with a comprehensive toolbox for a differentiated and in‐depth characterization of fluorescence signals. MTED was validated by analyzing astrocytic Ca 2+ activity across Ca 2+ indicators, imaging setups, and model systems from primary cell culture to awake, head‐fixed mice. We identified extended Ca 2+ activity at 25°C compared to 37°C physiological body temperature and dissected how neuronal activity shapes long‐lasting astrocytic Ca 2+ activity. Our MTED strategy, as a parameter‐free approach, is easily transferrable to other fluorescent indicators and biosensors and embraces the additional dimensionality of signaling activity strength. It will also advance the definition of standardized procedures and parameters to improve comparability of research data and reports. Main Points: pixel‐based multiple‐threshold analysis to quantify multidimensional biosensor and indicator readouts as ΔF/F0 handles dynamic and overlapping astrocyte Ca 2+ activity patterns few input parameters ease comparability and standardization